Analisa Faktor Yang Mempengaruhi Perkembangan Obligasi Korporasi di Indonesia - Syafri, Syafri (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2009)
The quarterly data of 1989-4-2007:4 was used to analyze the factors the factors that affected the development of the corporate bond in Indonesia. Using the multiple regression method, the regression results show that the development of the corporate bond is affected by the real income, nominal interest rate, the emergence of the secondary bond market and rating agency. Real income, the emergence of the secondary bond market and rating agency havea positive influence on the development of the corporate bond while nominal interest rate has a negative impact on it. The emergency of goverment bond and economic crisis have no impact on the development of the corporate bond